Fostering Entrepreneurship in Azerbaijan - Kuriakose, Smita (Washington, DC: World Bank, 2013)
A dynamic and vibrant private sector is crucial to economic growth, with firms making new investments, creating jobs, improving productivity, and promoting growth. Entrepreneurial activity is pivotal to the continued dynamism of the private sector, as the generation of new businesses fosters competition and economic growth. This is particularly relevant for Azerbaijan, whose government faces a central challenge to create conditions that will facilitate growth in nonoil tradable sectors. The core objectives of Azerbaijan's development strategy are to diversify the economy away from the oil sector and sustain high employment and growth. Encouraging high-growth entrepreneurship can help Azerbaijan achieve these goals as it moves toward new opportunities in value added and tradable sectors. This study shows that high-growth entrepreneurialism is low in Azerbaijan and that innovative activity among firms is very low. Several factors hinder business growth and entrepreneurship: lack of competition, especially among smaller firms; financial systems that are not conducive to business development. Companies cite high interest rates and risk-averse lending policies as substantial hindrances to expansion. In addition, risk capital is in short supply; and lack of industry-relevant skills. The government could play an important role by removing bottlenecks that impede entrepreneurialism in the general business environment as well as by designing new financial policy instruments that foster entrepreneurship and innovation. In doing so, the government needs to exercise care that the design and management of these instruments prevent capture or corruption and promote efficiency. Lack of competition is an issue in Azerbaijan, particularly for Small and Medium Enterprises (SMEs), which face uneven treatment within the enterprise sector.